2017
DOI: 10.1109/tps.2017.2704621
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Launch Package for the PEGASUS Launcher

Abstract: Abstract-Railguns are capable to far exceed the muzzle energies of current naval deck guns. Therefore one of the most promising scenario for the future application of railguns in naval warfare is the long range artillery. Hypervelocity projectiles being propelled to velocities above 2 km/s reach targets at distances of 200 km or more. At the French-German Research Institute the PEGASUS launcher is used for investigations with respect to this scenario. The 6 m long barrel has a square caliber of 40 mm. The powe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…During the railgun launch process, the in-born magnetic field will reach several T and keep several milliseconds. Besides, it generally presents a waveform of a trapezoid [7][8][9][10]. In previous railgun ammunition safety tests, two kinds of magnetic fields were mainly adopted.…”
Section: Introductionmentioning
confidence: 99%
“…During the railgun launch process, the in-born magnetic field will reach several T and keep several milliseconds. Besides, it generally presents a waveform of a trapezoid [7][8][9][10]. In previous railgun ammunition safety tests, two kinds of magnetic fields were mainly adopted.…”
Section: Introductionmentioning
confidence: 99%
“…For example, electromagnetic launchers (EMLs) or railguns have been developed to install battleships by the US Navy and the Chinese Navy since 1995 and 2011, respectively [1][2][3]. Moreover, the French-German Research Institute has developed the PEGASUS Launcher, having a 10-Mega Joule (MJ) pulse power system, to increase efficiency and high muzzle velocity [4][5][6]. The most attractive advantage of an EML is the ability to obtain higher projectile velocities than conventional gunpowder-type guns.…”
Section: Introductionmentioning
confidence: 99%
“…Within this research effort, it was demonstrated in the laboratory that velocities above 3 km/s are achievable [1]. Further on, a preliminary launch package design was developed and tested to show that hypervelocity projectiles can be launched using railguns [4]. In the longrange artillery scenario, the projectile is launched under a steep firing angle to reach the distant target on a ballistic trajectory.…”
Section: Introductionmentioning
confidence: 99%